URGENSI PENERAPAN VICTIM TRUST FUND TERHADAP KORBAN KEKERASAN SEKSUAL DI INDONESIA - Antonius Andrew Lysandro, (2023)
The enactment of Law Number 12 of 2022 on Sexual Violence Crimes (TPKS law) is an opening door for victims of sexual violence to achieve justice. Furthermore, Article 35 mentions a new system for Indonesian criminal justice, namely the Victim Assistance Fund or Victim Trust Fund where this system or mechanism has been implemented by several countries such as America, one of them. This research uses normative juridical research and uses legislation approach, conceptual approach, and comparative approach. The results of this study provide the position of victims in the Victim Trust Fund is very important and strong for the criminal justice system in Indonesia because it creates justice in a firm and binding. Although arrangements regarding Victim Trust Fund Schemes or mechanisms have not been clearly regulated in the Indonesian justice system, this is a good first step in fulfilling the rights of victims. Adjustments to the arrangements regarding the Victim Trust Fund can be made in accordance with the arrangements already in force in the United States, namely after the judge handed down the verdict and the victim can apply for the Victim Assistance Fund. In addition, other alternatives Victim Trust Fund can be put together with a series of reading the letter of demand so that the application of Victim Trust Fund can be implemented immediately.